2015
DOI: 10.1007/s00299-015-1791-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional feedback regulation of YUCCA genes in response to auxin levels in Arabidopsis

Abstract: The IPyA pathway, the major auxin biosynthesis pathway, is transcriptionally regulated through a negative feedback mechanism in response to active auxin levels. The phytohormone auxin plays an important role in plant growth and development, and levels of active free auxin are determined by biosynthesis, conjugation, and polar transport. Unlike conjugation and polar transport, little is known regarding the regulatory mechanism of auxin biosynthesis. We discovered that expression of genes encoding indole-3-pyruv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 66 publications
4
50
0
Order By: Relevance
“…The decrease in expression of YUC1 , YUC2 , YUC5 , YUC6 , and TAR2 , together with the effects of melatonin on auxin transport may cause the decrease in IAA levels in roots, at least partially. As reported recently, application of 1-naphthaleneacetic acid (NAA) and 2,4-dichlorophenoxyacetic acid (2,4-D) results in a decay in the transcript levels of YUC1 , YUC2 , YUC4 , YUC6 , and TAR2 in Arabidopsis seedlings (Suzuki et al, 2015). We noticed there is a difference in the endogenous IAA level between this study and previous results (Zhao et al, 2001; Lee et al, 2012), which could be resulted from two possible reasons.…”
Section: Discussionmentioning
confidence: 85%
“…The decrease in expression of YUC1 , YUC2 , YUC5 , YUC6 , and TAR2 , together with the effects of melatonin on auxin transport may cause the decrease in IAA levels in roots, at least partially. As reported recently, application of 1-naphthaleneacetic acid (NAA) and 2,4-dichlorophenoxyacetic acid (2,4-D) results in a decay in the transcript levels of YUC1 , YUC2 , YUC4 , YUC6 , and TAR2 in Arabidopsis seedlings (Suzuki et al, 2015). We noticed there is a difference in the endogenous IAA level between this study and previous results (Zhao et al, 2001; Lee et al, 2012), which could be resulted from two possible reasons.…”
Section: Discussionmentioning
confidence: 85%
“…27,34,37) We have recently reported that endogenous IAA is downregulated in response to the synthetic auxins 1-naphthaleneacetic acid (NAA) and 2,4-dichlorophenoxyacetic acid (2,4-D). 38) The feedback regulation of endogenous IAA is accompanied by downregulation of YUC gene expression. 38) Therefore, regulation of YUC gene expression is important in regulating the endogenous IAA level.…”
Section: Key Word: Arabidopsis; Auxin; Feedback-regulationmentioning
confidence: 99%
“…Arabidopsis seedlings were sterilized and grown at 21°C under continuous light and on half‐strength Murashige and Skoog (MS) medium (Invitrogen, Carlsbad, CA, USA) supplemented with 0.8% agar and 1% (w/v) sucrose. To measure primary root length, the wild‐type and YUC1‐overexpressor (Suzuki et al ., ) were grown for 7 or 9 days on agar medium containing 3 μ m of inhibitors in vertically oriented plastic plates. To measure free IAA, the wild‐type seedlings were grown for 6 days on vertically oriented agar medium, transferred to a culture tube containing liquid medium, incubated for 1 day with shaking, and treated with or without inhibitors dissolved in 0.1% (v/v) dimethyl sulfoxide (DMSO) for 3 h. To measure IPyA, the wild‐type seedlings were grown for 7 days on agar medium in vertically oriented plates, transferred to a culture tube containing liquid medium, incubated for 1 days with shaking, and treated with or without inhibitors dissolved in 0.1% (v/v) DMSO for 3 h. To assess gene expression of auxin markers, the wild‐type seedlings were grown for 6 days on vertically oriented agar medium, transferred to a culture tube containing half‐strength MS liquid medium with 1% sucrose, incubated for 1 day with shaking, and treated with 10 μ m inhibitors, 1 μ m IPyA and 100 n m IAA for 3 h. To test for recovery from growth defects caused by BBo or PPBo, wild‐type seedlings were grown 7 days on half‐strength MS plates in the presence of 3, 10 or 30 μ m BBo or PPBo in combination with 0, 1, 10 or 100 n m IAA.…”
Section: Methodsmentioning
confidence: 99%